Rotational modulation and single g-mode pulsation in the B9pSi star HD 174356?. Issue 1 (27th August 2020) - Mikulášek, Z; Paunzen, E; Hümmerich, S; Niemczura, E; Walczak, P; Fraga, L; Bernhard, K; Janík, J; Hubrig, S; Järvinen, S; Jagelka, M; Pintado, O I; et al.
ABSTRACT: Chemically peculiar (CP) stars of the upper main sequence are characterized by specific anomalies in the photospheric abundances of some chemical elements. The group of CP2 stars, which encompasses classical Ap and Bp stars, exhibits strictly periodic light, spectral, and spectropolarimetric variations that can be adequately explained by the model of a rigidly rotating star with persistent surface structures and a stable global magnetic field. Using observations from the Kepler K2 mission, we find that the B9pSi star HD 174356 displays a light curve variable in both amplitude and shape, which is not expected in a CP2 star. Employing archival and new photometric and spectroscopic observations, we carry out a detailed abundance analysis of HD 174356 and discuss its photometric and astrophysical properties in detail. We employ phenomenological modelling to decompose the light curve and the observed radial velocity variability. Our abundance analysis confirms that HD 174356 is a silicon-type CP2 star. No magnetic field stronger than 110 G was found. The star's light curve can be interpreted as the sum of two independent strictly periodic signals with $P_1=4{_{.}^{\rm d}}043\, 55(5)$ and $P_2=2{_{.}^{\rm d}}111\, 69(3)$ . The periods have remained stable over 17 yr of observations. In all spectra, HD 174356 appears to be single-lined. From the simulation of the variability characteristics and investigation of stars in the close angular vicinity, we put forth the hypothesis that the peculiar light variability of HD 174356 arises in a single star and is caused by rotational modulation due to surface abundance patches ( P 1 ) and g-mode pulsation ( P 2 ).